Chemical and biological transfer: Which one is responsible for the maternal transfer toxicity of tris(1, 3-dichloro-2-propyl) phosphate in zebrafish?. (December 2018) - Zhang, Yongkang; Su, Guanyong; Li, Meng; Li, Shuying; Wang, Qiangwei; Zhu, Guonian; Letcher, Robert J.; Liu, Chunsheng
Abstract: Maternal transfer toxicity of chemicals has mainly focused in fish on the chemical transfer from maternal generation to offspring, and limited information is available for the evaluation of effects of chemicals from a biological transfer perspective. In this study, first-generation (F0) zebrafish larvae ( D. rerio ) were exposed to 0, 50, 500 or 5000 ng/L TDCIPP from 14 days post fertilization (dpf) to 120 dpf. F0-generation zebrafish were paired, and F1-generation embryos were collected and continuously exposed to the same concentrations of TDCIPP until 150 dpf. F1-generation females were then paired with unexposed adult males, and maternal transfer effects on survival rate and body length were evaluated. Results demonstrated that maternal exposure to TDCIPP for two generations significantly decreased body length of F2-generation larvae, suggesting the occurrence of maternal transfer toxicity. The transfer of TDCIPP from maternal generation to offspring was evident, but microinjection of equal amounts of TDCIPP did not affect survival and body length of zebrafish larvae. Furthermore, maternal exposure to TDCIPP changed the concentrations of partial mRNAs and proteins in their eggs, and those changes were linked to maternal transfer toxicity (e.g., growth inhibition). These results suggested that in zebrafish changes in biological transfer may explain, at least in part, the observed maternal transfer toxicity of TDCIPP. Graphical abstract: Image 1 Highlights: Maternal transfer toxicity of TDCIPP was observed in zebrafish. The transfer of TDCIPP from maternal generation to offspring was evident. Maternal exposure to TDCIPP changed the concentrations of partial mRNAs and proteins in their eggs. Changes in biological transfer may explain, at least in part, the observed Maternal transfer toxicity of TDCIPP. Abstract : Exposure to TDCIPP caused maternal transfer toxicity, and alterations in biological transfer might be responsible for the toxic effects observed.